2020
DOI: 10.1186/s12877-020-1454-y
|View full text |Cite
|
Sign up to set email alerts
|

Information needs and information seeking behaviour of people with dementia and their non-professional caregivers: a scoping review

Abstract: Background: People with dementia often require full-time caregivers especially in the later stages of their condition. People with dementia and caregivers' access to reliable information on dementia is essential as it may have an important impact on patient care and quality of life. This study aims to provide an overview of the information needs and information seeking behaviour of people with dementia and their non-professional caregivers. Methods: We conducted a scoping review of the literature and searched … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 49 publications
9
98
0
7
Order By: Relevance
“…Overall, participants identified health information needs that focused on getting through the day, what the future holds, and treatment plans. Similar findings have been reported in previous studies of caregivers, including help with daily management (Huis et al, 2018;Werner et al, 2017), disease progression (Killen et al, 2016), and information on treatment options and clinical trials (Soong et al, 2020). Differences in health information needs between persons living with dementia and caregivers in this study were few, similar to previous findings that persons living with dementia and caregivers had an 80 percent overlap in information needs (Edelman et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, participants identified health information needs that focused on getting through the day, what the future holds, and treatment plans. Similar findings have been reported in previous studies of caregivers, including help with daily management (Huis et al, 2018;Werner et al, 2017), disease progression (Killen et al, 2016), and information on treatment options and clinical trials (Soong et al, 2020). Differences in health information needs between persons living with dementia and caregivers in this study were few, similar to previous findings that persons living with dementia and caregivers had an 80 percent overlap in information needs (Edelman et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Persons living with dementia focused on understanding and appraising health information related to treatment and disease progression. These findings that persons living with dementia wanted information related to treatment and clinical trials were similar to findings reported by Soong et al (2020). Caregivers, too, were concerned about treatment and dementia progression, but they also wanted information about life tips for daily management of dementia, similar to earlier reports (Mountain & Craig, 2012;Soong et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Across all of these sources of information, participants identified a range of information needs that fit into four broad themes related to health care (e.g., information about illnesses causing dementia, how to recognize symptoms and how to act upon symptoms, how to work with healthcare teams, and medical and nonmedical treatments); care and support (e.g., the availability of social and other support services and how to access those services, safety considerations, and care options including long-term care placement); living well (e.g., how to transform and live with the emotional reactions of the diagnosis such as grief, loss, and anger, how to enhance communication, and how to maintain holistic wellness and quality of life in order to live well with the diagnosis); and planning ahead (e.g., how to manage activities and strategies for planning ahead including dealing with financial consequences of the diagnosis, designating powers of attorney, and end of life care). These themes are similar to those found in a recent study by Soong et al (2020). Given the differences in terms of availability of support services and processes for accessing those services across Canada, the PAR team had a number of conversations at this stage to determine how best to discuss information related to the theme of care and support.…”
Section: Identification Of Information Needssupporting
confidence: 57%
“…However, written materials can often be difficult to get into the hands of persons newly diagnosed, leaving many without the information they need for effective self-management. Internet-based resources are increasingly becoming a primary source of information and advice (Allegrante et al, 2019), including with persons living with dementia and their care partners (Soong et al, 2020) and older adults (Flynn et al, 2006: Medlock et al, 2015). Advantages of sharing information via the internet include increased accessibility, interactivity, information tailoring, privacy and anonymity, and providing a more graphically and aesthetically engaging experience (Allegrante et al, 2019).…”
Section: Self-management Approaches and Resourcesmentioning
confidence: 99%